Flame‐retardant behavior and mechanism of the SBR/MMT composites modified by melamine matrix modifier. Issue 27 (24th February 2021) - Cheng, Guojun; Xuan, Ziyue; Tang, Zhongfeng; Tian, Shen; Sha, Feixiang; Ding, Guoxin; Wan, Xianglong
Abstract: Melamine quaternary ammonium salt (MQAS), a novel flame‐retardant intercalation modifier, was used to prepare the flame‐retardant organic montmorillonite (FOSM), and which was added to SBR by a two‐roll mixing and molding process to prepared the SBR/FOSM composites. The synergistic flame‐retardant effects of sodium‐based montmorillonite (MMT) and MQAS were investigated by the various methods. The LOI value of SBR was only 19.1%, and FOSM‐4 increased the LOI value of SBR to 24.3%. The cone calorimetry test showed that compared with SBR, the total heat release and the peak heat release rate of SBR/FOSM were reduced by 81.39% and 86.08%, respectively. The analysis of MMT after modification showed that the grafting rate of MQAS was about 10% and the interlayer spacing of MMT was enlarged by about 20%. The synergy of MQAS and MMT not only effectively solves the violent droplet of pure SBR combustion, but also avoids the curling problem of only adding MMT. The char morphology and TG‐FTIR showed that FOSM had dual flame‐retardancy in the condensed phase and the gas phase. The synergistic flame‐retardant effect of phosphorus‐free flame‐retardant modifier and MMT will open up new possibilities for flame‐retardant elastomer composites. Abstract : Melamine quaternary ammonium salt (MQAS) was Intercalated into montmorillonite (MMT) as a flame retardant modifier in Butadiene Styrene Rubber(SBR). Together, MQAS acted as flame retardantsby absorbing heat and MMT could prevent heat penetration to the SBR. Therefore, the synergistic flame‐retardant effect of phosphorus‐free flame‐retardant modifier and MMT will open up new possibilities for flame‐retardant elastomer composites.